Differentiation of Proceedings in the Court of First Instance under the Statute of Criminal Procedure of 1864 - OBORONOVA, Iryna (University Scientific Notes, 2021)
The provisions of Statute of criminal procedure devoted to the differentiation of criminal proceedings in the court of first instance are analyzed in the article. The author accentuates that the current criminal procedure legislation of Ukraine has inherited a lot of progressive ideas implemented by Statute of criminal procedure; in particular, it contains a number of differentiated procedures for criminal proceedings in the court of first instance. In fact, Statute of criminal procedure provided for three types of criminal proceedings: ordinary, simplified and complicated, as well as some peculiarities in certain categories of proceedings. Simplified procedure was provided for the consideration of cases of minor criminal offenses — in proceedings before a magistrate (there were signs of private prosecution) and proceedings in absentia in the court of first instance. In addition, such a procedure included an abbreviated judicial investigation, which is carried out in the general order of the trial (summary trial). A complicated procedure took place in the trial court with the participation of jurors, which separated the powers of the jury to pass a verdict and the judge — to pass sentence. The criteria for distinguishing between proceedings according to the degree of complexity of procedural forms were: the nature and severity of the criminal offense, the ratio of private and public interests, as well as the category of cases that could be considered by a jury. The Statute of criminal procedure also contained exceptions to the general procedure of criminal proceedings, which provided for peculiarities in certain categories of proceedings (in cases involving the clergy, the military, state crimes, official crimes, etc.). The criteria for distinguishing such features were: the status of the accused (clergy, military), as well as the category of cases (for crimes against religion and others related to violation of church rules, for state crimes, for official crimes, for crimes in administrative management sphere).
Keywords: differentiation; court proceedings; court of first instance; proceedings in absentia; summary trial; jury trial; Statute of criminal procedure